Characterization and evaluation of biological Activities of silver nanoparticle using Wattakaka volubilis linn.f. - WASEEM IQBAL KHANDAY,; EYINI MUTHUKUMARASAMY,; BALAJI PAULRAJ, (International Journal of Pharma and Bio Sciences, 2016)
The dried leaves of Wattakaka volubilis was used for the synthesis of silver nanoparticles and evaluation of their antibacterial and antioxidant biological activities. The silver nanoparticles were characterized by UV-visible and Fourier transform infra-red spectroscopy (FTIR). The antibacterial activity of 1mM concentration of the silver nanoparticles against Escherchia coli produces 18mm zone of inhibition and against Bacillus subtilis and Staphylococuss aureus produces 17mm zone of inhibition at 50μg/ml concentration. Among the different concentration,1mM silver nanoparticles showed the highest anti-oxidant activity of 92.98% at 100μg/ml and thus being a good electron donor silver nanoparticles showed highest reducing power activity with optical density value of 0.144 at 100μg/ml.